Measurements on polar liquids at a microwave frequency — evaluation of molecular parameters — a new method - Murthy, M. B. R.; Dyasagar, B. S.; Patil, R. L. (2003)
A simple method of estimating the dipole moment (mu) and relaxation time (tau) of polar. molecules in liquid state, from a single set of dielectric measurements at high frequency, is proposed by using the concept of dielectric virial coefficients and employing Onsager model. The proposed method is tested in a number of polar liquids and the results are discussed.